THE PROTECTION OF CONSTITUTIONAL RIGHTS THROUGH THE PRACTICE OF JUDICIAL ACTIVISM IN THE CONSTITUTIONAL COURT - Hikam Hulwanullah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
According to the democracy index, Indonesia is a flawed democracy, meaning that, as the state's organ of governance, the government is still insufficiently powerful to effectively defend the fundamental rights of its people. One of the causes of this is the inadequate legal system and protection of citizens' fundamental rights from the state, which is essentially achieved through the practice of judicial activism at the Constitutional Court. This study utilizes normative research to examine written regulations' norms to provide findings about the pressing need to address the practice of judicial activism at the Constitutional Court. This study utilized three distinct sorts of approaches: the statute approach, the conceptual approach, and the comparative approach. Moreover, relevant primary, secondary, and tertiary legal documents serve as the foundation for this study. After gathering this legal data through a review of the literature, qualitative descriptive and comparative descriptive analytic methodologies were used for analysis. The author found that judicial activism is one of the steps that judges can take to make efforts to protect the constitutional rights of citizens in the constitutional court.